Communication strategy use by healthcare trainees in monologues and dialogues during strategy training - Megawati, Soekarno; Ting, Su Hie (Centre for Applied Language Studies, 2016)
The study examined the use of communication strategies in monologues and dialogues by Malaysian healthcare trainees with limited English proficiency during communication strategy training. The training focused on the use of circumlocution in individual presentation, appeal for assistance in role-play, offering assistance and lexical repetition in group discussion, stress (tonicity) in responding to questions after a presentation, and filled pauses in interviews. The speech of eight participants in the five speaking tasks were recorded and transcribed. The analysis of the 6,137-word transcript showed that monologues called into use more communication strategies than dialogues which are jointly negotiated. The participants used pauses and lexical repetition as communication strategies most often, which, in fact, is predictable considering their language proficiency. Most of the pauses were pauses filled with sounds like umm and uhh rather than fillers taught during the strategy training. The analysis revealed that the participants could use lexical repetition to appeal for assistance, request clarification and confirm comprehension but the frequencies for these strategies were low compared to discourse maintenance and topic salience marking. The strategy training helped the participants to use the strategy that was taught immediately after the training but automatisation in strategy use had not taken place.